Intramolecularly double-donor-stabilized stannylene and its coordination towards Ag(I) and Au(I) centers - Chibde, Purva; Raut, Ravindra K.; Kumar, Vikas; Deb, Rahul; Gonnade, Rajesh; Majumdar, Moumita (Chemistry-An Asian Journal, 2021)
The intramolecularly double-donor-stabilized stannylene 1 has been synthesized from the salt-metathesis reaction between two equivalents of lithium pyridine ene-amide L1 and SnCl2. Compound 1 exhibits dipolar behavior when reacted with B(C6F5)(3) leading to the zwitterionic compound 2. The reaction of 1 with one equivalent and 0.5 equivalent of AgOTf (OTf=trifluoromethane sulfonate) result in the formation of a stannylene-AgOTf complex 3 and a homoleptic distannylene-silver ionic complex 4, respectively. Analogous to complex 4, the gold(I) complex 5 has been synthesized from the reaction between two equivalents of 1 and 0.5 equivalent of AuCl.SMe2/Me3SiOTf. Complex 5 is the first example of homoleptic stannylene-Au(I) ionic complex among the very scarce reports on stannylene-gold(I) coordination complexes. All compounds have been structurally characterized using single crystal X-ray crystallography. Solution-state characterization have been performed using multinuclear NMR techniques. Detailed DFT calculations on the optimized geometries 1 o, 3 o-5 o reveal the change in sp- hybridization on the pyramidal Sn(II) center upon metal coordination and their bonding overlaps.
Keywords: coordination; gold cation; hybridization; intramolecular donor; stannylene